Istibdal Waqf: Sentiment Analysis - Siti Fatimah Azzahro (The Economic Review of Pesantren, 2022)
Land waqf in Indonesia continues to grow, but there are waqf lands that are unproductive because they are located in not strategic areas, so there is a need for Ibdal or Istibdal Waqf but, there are differences of opinion from some Muslim scholars regarding Ibdal or Istibdal. So, there is a need for sentiment analysis to find out sentiment on topic of Ibdal or Istibdal. The method of this study is a descriptive statistical analysis method combined with meta-analysis and sentiment analysis of secondary data in the metadata of 44 publications from Dimension from 2010-2022, processed using Microsoft Excel 2016 and SentiStrength software. The results of the research sentiment analysis regarding Istibdal Waqf are positive 9%, Neutral 45%, and Negative 46%. The author found research on istibdal Waqf from year to year has increased. The results of this study indicate that there is negative sentiment regarding Istibdal Waqf, indicating that literacy regarding support for Istibdal waqf is still low so massive socialization is needed for the community or to Nazhir as the waqf manager. The power of laws and technical guidelines that regulate Istibdal are also needed by the Nazirs so that the flow of execution is easier, to create optimal waqf land.